Non-clinical outcome measures in dentistry: publishing trends 1988–98 - Buck D, Newton JT (Blackwell Synergy, 2001)
To provide an overview of the use of non-clinical outcome measures in dentistry and to identify trends and strengths and weaknesses in existing research. Methods: Literature searches using medical and social sciences databases and stated inclusion and exclusion criteria.